2006
DOI: 10.1177/0363546506290404
|View full text |Cite
|
Sign up to set email alerts
|

Long–term Results of Arthroscopic Bankart Repair with a Bioabsorbable Tack

Abstract: Arthroscopic Bankart repair for the treatment of recurrent traumatic anterior shoulder instability repair using bioabsorbable tacks offers reliable results with respect to failure rate, range of motion, and shoulder function during a minimum follow-up of 7.0 years. In contrast to previous reports on arthroscopic Bankart repair, results did not deteriorate during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 37 publications
3
22
0
1
Order By: Relevance
“…The frequency of recurrent instability in our study seems comparable to other published series of arthroscopic instability procedures in which a simple sling was used [10,13,16], but without a head-to-head comparison in the setting of a single study, this inference should be interpreted cautiously.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The frequency of recurrent instability in our study seems comparable to other published series of arthroscopic instability procedures in which a simple sling was used [10,13,16], but without a head-to-head comparison in the setting of a single study, this inference should be interpreted cautiously.…”
Section: Discussionsupporting
confidence: 83%
“…Another series by Law et al [13] of 38 patients with an average age of 21 years at mean 28 months after arthroscopic Bankart repair for anterior shoulder instability recorded an average WOSI score of 83%, which is similar to our mean WOSI of 86.8%. In a series of 18 patients with a mean age of 26.8 years, Marquardt et al [16] reported a mean ASES score of 92.1 at mean 8.7 years after surgery. The mean SF-12 PCS score at final followup of 54.7 ± 0.8 was higher than the national mean of 53.3 for the 25-to 34-year-old age group [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite encouraging initial results, follow-up studies revealed multiple complications including migration, loosening, breakage of metal suture anchors (which can lead to severe degenerative joint damage), and interference with magnetic resonance imaging [12,25]. To solve the problem posed by metal anchors, the use of bioabsorbable anchors has been increasing [20,23]. Barber et al [6] reported several advantages of bioabsorbable anchors, including resorption, radiotranslucency (which facilitates imaging), reduced revision surgery rate, and minimum migration.…”
Section: Introductionmentioning
confidence: 99%
“…1,14,27,34 The incidence of glenohumeral arthrosis after conservative treatment of traumatic anterior shoulder dislocation in a long-term follow-up of 25 years has been reported to be as high as 60% (97 of 161 shoulders). 15 Although the results after long-term follow-up of arthroscopic Bankart repair have been reported widely, 5,6,12,19,20,23,24,26,27,33 the focus in these studies has been on the functional outcome and joint stability whereas the occurrence of glenohumeral arthrosis after surgery has not been studied in detail. The aim of our study is to establish the radiologic and clinical occurrence of glenohumeral arthrosis after arthroscopic Bankart repair.…”
mentioning
confidence: 99%